The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1111/ics.12923
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical epilation exerts complex biological effects on human hair follicles and perifollicular skin: An ex vivo study approach

Marta Bertolini,
Jennifer Gherardini,
Jérémy Chéret
et al.

Abstract: ObjectiveElectrical epilation of unwanted hair is a widely used hair removal method, but it is largely unknown how this affects the biology of human hair follicles (HF) and perifollicular skin. Here, we have begun to explore how mechanical epilation changes selected key biological read‐out parameters ex vivo within and around the pilosebaceous unit.MethodsHuman full‐thickness scalp skin samples were epilated ex vivo using an electro‐mechanical device, organ‐cultured for up to 6 days in serum‐free, supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 174 publications
(262 reference statements)
0
1
0
Order By: Relevance
“…Recently, it has been shown that mechanical epilation removes most of the hair shafts, often together with fragments of the outer and inner root sheath and hair matrix. This mechanically induced trauma to the hair follicle triggers complex biological responses [6]. These range from increased hair follicle keratinocyte apoptosis to differentially expressed key players of skin inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that mechanical epilation removes most of the hair shafts, often together with fragments of the outer and inner root sheath and hair matrix. This mechanically induced trauma to the hair follicle triggers complex biological responses [6]. These range from increased hair follicle keratinocyte apoptosis to differentially expressed key players of skin inflammation.…”
Section: Introductionmentioning
confidence: 99%